Temperature stability study of killed, bivalent, oral cholera caccine, shanchol in Bangladeshi adult participants - Ahmed, Sadia (BRAC University, 2014)
This thesis submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.